2019
DOI: 10.3390/nu11102333
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Nutrients and Food Products Intake of Polish Males with Ulcerative Colitis in Remission

Abstract: In spite of the lack of evidence of diet therapy efficacy to sustain remission of ulcerative colitis (UC), the dietary counseling may be beneficial, as a number of patients restrict intake of some products with no medical consultation. The aim of the present study was to analyze the nutrients and food products intake of Polish males with UC in remission in comparison with a control group. The UC group of 44 male patients with the confirmed remission, as well as the pair-matched group of 44 male controls, match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Protein-energy wasting is observed more frequently in IBD patients than in healthy individuals, and the same observation can be made in Crohn’s disease patients as compared to subjects suffering from ulcerative colitis [ 33 ]. There were no statistically significant differences between men with ulcerative colitis in remission and healthy subjects [ 34 ].…”
Section: Proteins Fats and Carbohydrates Intake In Ibd And The Rmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein-energy wasting is observed more frequently in IBD patients than in healthy individuals, and the same observation can be made in Crohn’s disease patients as compared to subjects suffering from ulcerative colitis [ 33 ]. There were no statistically significant differences between men with ulcerative colitis in remission and healthy subjects [ 34 ].…”
Section: Proteins Fats and Carbohydrates Intake In Ibd And The Rmentioning
confidence: 99%
“…There was no statistically significant differences in the intake of total fat, saturated fat, and mono–and poly–unsaturated fat between healthy individuals and CU patients [ 34 ]. The European Society for Clinical Nutrition and Metabolism does not recommend n-3 fatty acid supplementation for maintaining remission in IBD [ 27 ].…”
Section: Proteins Fats and Carbohydrates Intake In Ibd And The Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower intake of vitamin C may be due to a reduced intake of fresh vegetables and fruits. However, Głąbska et al reported that the intake of vegetables and fruits, as well as of vitamin C does not significantly differ between men suffering from ulcerative colitis (UC) and the healthy individuals [16]. Table 2 shows the average intake of vitamin C among patients with CD or UC and healthy.…”
Section: Vitamin C Deficiency In Ibd Patients and The Risk Of Osteopomentioning
confidence: 99%
“…The habitual intake was assessed with no specific dietary intervention conducted. The dietary intake was assessed based on the three-day dietary records that were conducted by the participants during three typical, random, but not consecutive days, two of them being week days and one a weekend day [25]. Participants received structured forms with the detailed instructions, and the self-reported data were gathered.…”
Section: Dietary Intakementioning
confidence: 99%